HUBUNGAN PEMAHAMAN TENTANG PERUBAHAN FISIK DENGAN KECEMASAN REMAJA YANG MEMASUKI USIA PUBERTAS DI SMP N 3 KLATEN - Antonius Giri Bawono (STIKES DUTAGAMA KLATEN, 2017)
Background: Most of people know puberty stage and everyone has to experience it. However, in that time they feel anxious because of physical changes. But then some of them are more aware about physical change in puberty stages. Objective: The objective of this research is to determine the level of understanding of the physical change at puberty stages, the teenage anxiety level in SMPN 3 Klaten, and to determine the relationship between them when entering puberty stages at SMPN 3 Klaten. Research Methods: This research is a quantitative research methods with associative Cross-sectional model approached. The population in this research are the Seventh and Eighth grader students of SMP N 3 Klaten, which totaled 507 students. While samples teken totaled 84 students with Simple Random Sample technique. The data of understanding level collected by measuring it with questionnaire and the teenage anxiety data used the HRS-A. The statistical test used the Chi-Square Test. The Result Of Research: The result of research shows that there was a significant relation between understanding physical change level with the teenager anxiety when entering puberty stages at SMPN 3 Klaten, with a significance p-value of 0.000, because (0.000 <0.05), then H0 is rejected and Ha accepted. This means that there is a significant relation between the understanding of the physical changes and teenage anxiety in puberty stage at SMP 3 Klaten. Any effect on the level of understanding of anxiety, then anxiety experienced by respondents is the result of understanding the respondents earned Conclusion: There is a significant relationship between physical change understanding and the teenage anxiety when entering puberty stage at SMPN 3 Klaten